Natural feed additive containing Saccharomyces cerevisiae-originated free nucleotides improves innate immunity, gut histology and disease resistance in Nile tilapia - Barducci, Robson Sfaciotti; de Abreu, Vanderlei; Santos, Anderson Aparecido Dias; Pacheco, Letícia Graziele; Koch, João Fernando Albers; Florencio, Moisés; Pilarski, Fabiana [UNESP] (Elsevier, 2022)
A 60-day feeding trial was conducted to assess the effects of dietary Saccharomyces cerevisiae-originated free nucleotides on growth, innate immunity, intestinal histomorphometry and disease resistance in Nile tilapia, Oreochromis niloticus (average initial weight of 7.85 g). Five diets (treatments) were prepared: negative control diet (NCD) - basal diet without additives; positive control diet (PCD) - basal diet supplemented with a commercial nucleotide-based additive at 170 ppm; and three experimental diets, N170, N320 and N470, supplemented with S. cerevisiae-originated free nucleotides at 170, 320 and 470 ppm, respectively. There were no significant differences in production parameters after the trial period. Nevertheless, the complement hemolytic activity was higher in fish subjected to the three experimental diets, while serum lysozyme concentration was higher in the N470 group compared with both controls. Intestinal villi height and density were greater in fish fed the N470 diet compared with the NCD group. In addition, fish receiving the three experimental diets showed higher absorption surface area magnification ratio, with the greatest values being observed in the N470 group. Lastly, the highest survival rate following Aeromonas hydrophila challenge was recorded in the N470 group. Taken together, the present findings indicate that supplementation of feed with S. cerevisiae-originated free nucleotides at 470 ppm improves non-specific immune responses and intestinal microstructure morphology as well as increases survival rate after bacterial infection in Nile tilapia. Therefore, this blend of natural nucleotides has the potential of being used as an alternative to antimicrobials when included as an additive in aquaculture feeds.
Keywords: Aquaculture feed; Fish disease; Gut histology; Innate immunity; Nucleotide; Yeast